PERTANIAN PADI BEBAS PESTISIDA KIMIA: EDUKASI DAN PENERAPAN PENGENDALIAN HAMA TERPADU (PHT) DI DESA BAWOZA’UA, NIAS SELATAN - Ridho Victory Nazara; Putra Hidayat Telaumbanua; Helmin Parida Zebua; Dian Agung Sanora Laia; Natalia Kristiani Lase; Yoel Melsaro Larosa; Yarman Gulo; Robert Alberth Sole (Universitas Nias Raya, 2025)
This community service program was carried out with the primary goal of enhancing the capacity and self-reliance of rice farmers in implementing the concept of Integrated Pest Management (IPM) based on environmentally friendly principles. Through this approach, farmers are expected to reduce their dependence on chemical pesticides, which have long posed potential negative impacts on health, the environment, and the ecological balance of paddy field ecosystems. The program was implemented through a seven-session workshop consisting of interactive lectures, group discussions, field demonstrations, and hands-on practice. Each session focused on improving farmers’ knowledge and practical skills, such as identifying natural pest enemies, utilizing botanical pesticides, and applying rice cultivation techniques that support IPM systems. Evaluation was conducted using a pre–post test on six indicators of knowledge and behavioral intention. The results showed a significant improvement: five out of six indicators reached a success rate above 80%, while farmers’ commitment to reducing chemical pesticide use reached 76%. These outcomes are consistent with recent literature (FAO, 2022; IRRI, 2020; Rahman et al., 2023), which highlights the effectiveness of IPM and the importance of participatory extension approaches in promoting sustainable agricultural practices. The program recommends continued mentoring, particularly in the production of botanical pesticides and the implementation of synchronized planting strategies, to strengthen the resilience of local agricultural ecosystems.